Dimensiunea europeană a educatiei civice. Cazul Bulgariei [Articol] - Radoykova, Gergana (CEP USM, 2022)
În 2020, în Bulgaria a fost introdusă o materie obligatorie – Educația civică. Ea vizează nu numai o orientare practică pentru statul democratic modern, separarea puterilor și statul de drept, ci și interpretarea acestora. O atenție sporită acordată formării culturii politice urmărește să-i ajute pe tineri să crească ca cetățeni activi și conștienți. Dimensiunea europeană a acestui subiect, și anume dobândirea cunoștințelor de bază despre natura și funcționarea UE, precum și înțelegerea valorilor nemateriale ale UE, este cheia acestui proces.

In 2020, a compulsory subject of civic education was introduced in Bulgaria. It is aimed not only at a practical orientation for the modern democratic state, separation of powers and rule of law, but also at their interpretation. Greater attention to the formation of political culture aims to help young people grow as active and aware citizens. The European dimension of this topic, namely the acquisition of basic knowledge about the nature and functioning of the EU, as well as the understanding of the non material values of the EU, is the key in this process.
EUROPEAN DIMENSION OF THE CIVIC EDUCATION. THE CASE OF BULGARIA
Keywords: Uniunea Europeană; Bulgaria educație civică; valori; identitate; European Union; Bulgaria civic education; values; identity